PENGARUH RASA KEBERSAMAAN TERHADAP TINGKAT PARTISIPASI MASYARAKAT DALAM PROGRAM PLP-BK (NOTO DESO) - Putra, Arya Dwihening (Jurusan Perencanaan Wilayah dan Kota, 2013)
In the flow of time, planning theory start to grow from only physical planning into a social one. According to John Friedman, planning divided into two kind of theory, they are top down and bottom up. Grounded on that conditions, masters of planning start to develop new and practical method to improve social, economic, and culture condition in terms of leading the bulding of civic society. This was the beginning of the community development. This reseacrh is trying to do a full observation in government program of community development called PLP-BK or people used to call noto deso that held in Kutoharjo District Kendal Regency. The objection of this research is to prove that the community sentiment is related and have a big influence to the rate of participation in implementation of noto deso itself. To identificate that matter this research is using a quantitative descriptive method and with self administered quisionare data gathering method. With the usage of that kind of research method, research variable can be identificate succesfully in order to processed in bivariate correlation analysis to prove the influence of community sentiment and the rate of participation. The outcome show us a fact that grounded on the correlation process the hypothesis of this research is proven that the community sentimet is really have a great influence to the rate of people participation in the implementation of noto deso program that held in Kutoharjo District. With the knowledge of that community sentiment influences the rate of participation, congruity progress in planning can be indentificate and the engineer the building of social can be optimalized in order to gain the civic society.